Belief in and concept of predestination: A critical analysis from Islamic perspective - Khan, Israr Ahmad (2012)
Muslims are lagging behind in many areas in the today’s world. One main reason for that is the concept of and belief in Predestination. This concept of and belief in Predestination is consequent upon interpretation of certain verses in the Qur’an and certain sayings of the Last Prophet (s.a.w.). Eleven verses from the Qur’an and five traditions of the Prophet (s.a.w.) that are generally advanced by fatalists have been selected for the analysis to see whether there is room in Islamic life for the concept of predetermination in the sense of fatalism.